Ratiometric fluorescent nanosensor based on carbon dots for the detection of mercury ion. (25th May 2018) - Ma, Yusha; Mei, Jing; Bai, Jianliang; Chen, Xu; Ren, Lili
Abstract: A novel ratiometric fluorescent nanosensor based on carbon dots has been synthesized via bonding rhodamine B hydrazide to the carbon dots surface by an amide reaction. The ratiometric fluorescent nanosensor showed only a single blue fluorescence emission around 450 nm. While, as mercury ion was added, due to the open-ring of rhodamine moiety bonded on the CDs surface, the orange emission of the open-ring rhodamine would increase obviously according to the concentration of mercury ion, resulting in the distinguishable dual emissions at 450 nm and 575 nm under a single 360 excitation wavelength. Meanwhile, the ratiometric fluorescent nanosensor based on carbon dots we prepared is more sensitive to qualitative and semi-quantitative detection of mercury ion in the range of 0–100 μ M, because fluorescence changes gradually from blue to orange emission under 365 nm lamp with the increasing of mercury ion in the tested solution.